Perspectives on Meaning in Music Therapy - Stige, Brynjulf (Voices: A World Forum for Music Therapy, 2003)
In this article I discuss some questions on meaning in music therapy by taking as my point of departure the different perspectives of two British music therapists, Mary Priestley and Gary Ansdell. Since all discussions of meaning - even when considering "non-verbal phenomena" - are based on an understanding of language, I have found the philosophy of Ludwig Wittgenstein an interesting port of entry to this topic. Following an introduction to Wittgenstein's concepts of "language game" and "family resemblances", I give a brief discussion of Wittgenstein's relevance for aesthetic understanding, highlighting the concept of "intransitive understanding". These three concepts will then be used as a basis for examining the differences between Priestley's and Ansdell's perspectives, which may serve to expand our thinking about meaning in music therapy.